Brake Anti-slide Detection and Protection for Metro Vehicles - YU Jieren; QIAN Hua; XIA Shuai; SHAO Yuehu; LI Yiye (机车电传动)
Based on the weakness analysis of the traditional wheel-slip detect methods such as speed difference and decelerationcriterion, proposals were given for the reference speed calculation and over sensitive caused by deceleration-criterion. At the same time, two different strategy of anti-slide recovery were compared, and their influence on the anti-slide efficiency and reference speed was analyzed. Finally, a new combined WSP strategy with both advantages is suggested.